Coexistence phenomenon of Ce3+–Ce4+ and Eu2+–Eu3+ in Ce/Eu co-doped LiBaB9O15 phosphor: luminescence and energy transfer. Issue 5 (23rd January 2017) - Li, Ting; Li, Panlai; Wang, Zhijun; Xu, Shuchao; Bai, Qiongyu; Yang, Zhiping
Abstract : Ce/Eu-doped LiBaB9 O15 (LBB) samples were prepared via conventional high temperature solid state reactions. Abstract : Ce/Eu-doped LiBaB9 O15 (LBB) samples were prepared via conventional high temperature solid state reactions. The XRD patterns, crystal structures, luminescence properties, and decay times were investigated systematically. Ce 3+ ions exist in LBB: x Ce 3+ that were synthesized in a reducing atmosphere and in an air atmosphere. However, we observed Eu 2+ ions in LBB: y Eu 2+ in a reducing atmosphere and Eu 3+ ions in LBB: z Eu 3+ in an air atmosphere. LBB:0.05Ce 3+, y Eu 2+ phosphors synthesized in a reducing atmosphere only possess Ce 3+ and Eu 2+ and exhibit a broad excitation band ranging from 350 to 425 nm. A reduction phenomenon of Eu 3+ → Eu 2+ and coexistence of Ce 4+, Ce 3+, Eu 2+ and Eu 3+ were observed when LBB:0.05Ce, w Eu phosphors were synthesized in an air atmosphere. There are three processes in LBB:0.05Ce, w Eu, i.e., energy transfers from Ce 3+ to Eu 2+ and from Eu 2+ to Eu 3+, and metal–metal charge transfer (MMCT) between Ce 3+ and Eu 3+ . Moreover, the MMCT process is dominant in LBB:0.05Ce, w Eu due to less efficient energy transfer from Ce 3+ to Eu 2+ . Moreover, the CIE coordinates of LBB:0.05Ce, w Eu vary systematically from light blue (0.313, 0.129) to red (0.589, 0.315) for LBB:0.05Ce 3+, w Eu synthesized in air with the changes in Eu ion concentration. Thus, we can control the color by controlling the synthesis atmospheres.